2016
DOI: 10.1259/bjr.20150743
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of breast lesions in a selective diagnostic population: diagnostic accuracy study for comparison between one-view digital breast tomosynthesis and two-view full-field digital mammography

Abstract: Objective: To compare the performance of one-view digital breast tomosynthesis (DBT) and two-view full-field digital mammography (FFDM) in the detection and characterization of breast lesions in a selective diagnostic population. Methods: A total of 598 breasts of 319 diagnostic patients were prospectively enrolled. Participants underwent bilateral one-view, mediolateral oblique (MLO) DBT and two-view, craniocaudal and MLO FFDM. The sensitivity and specificity of these methods and their classification into cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The reported sensitivity and specificity of DBT (88.7%, 93.8%) in stand‐alone mode, however, was predominantly higher as compared to DM . Also, one‐view DBT was found to be superior for dense breasts when compared with two‐view DM . DBT has also been linked with increased radiologists’ confidence in the assessment clinic …”
Section: Results: Use Of Dbt In Assessment Clinicmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported sensitivity and specificity of DBT (88.7%, 93.8%) in stand‐alone mode, however, was predominantly higher as compared to DM . Also, one‐view DBT was found to be superior for dense breasts when compared with two‐view DM . DBT has also been linked with increased radiologists’ confidence in the assessment clinic …”
Section: Results: Use Of Dbt In Assessment Clinicmentioning
confidence: 99%
“…20 Also, oneview DBT was found to be superior for dense breasts when compared with two-view DM. 38 DBT has also been linked with increased radiologists' confidence in the assessment clinic. 37 A study focusing primarily on distinct assessment of breast cancers, reported statistically significant improvement in radiologists' diagnostic performance with DBT (combined mode with DM) as compared to DM alone.…”
Section: Results: Use Of Dbt In Assessment Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Sixteen studies [12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] met our predefined inclusion criteria and were included in the evidence synthesis. The meta-analysis was performed separately for 5 diagnostic studies, and for 11 screening studies (these were examined separately for 8 screening studies that used two independent study groups, and the 3 screening studies that used one study group).…”
Section: Study Inclusionmentioning
confidence: 99%
“…Digital breast tomosynthesis (DBT) is rapidly gaining in popularity worldwide due to its high spatial‐resolution tomographic images of the breast and its ability to create reconstructions using multiple low‐dose projection images . Early clinical trials show improved sensitivity and specificity of DBT compared with digital mammography (DM) . Bakic et al determined that breast density may be accurately estimated using central DBT and found substantial inter‐ and intrareader agreement in breast density estimation between DM and central DBT projection images.…”
Section: Introductionmentioning
confidence: 99%